2021
DOI: 10.3389/fcvm.2021.763858
|View full text |Cite
|
Sign up to set email alerts
|

Expression Signatures of Long Noncoding RNAs in Left Ventricular Noncompaction

Abstract: Long noncoding RNAs have gained widespread attention in recent years for their crucial role in biological regulation. They have been implicated in a range of developmental processes and diseases including cancer, cardiovascular, and neuronal diseases. However, the role of long noncoding RNAs (lncRNAs) in left ventricular noncompaction (LVNC) has not been explored. In this study, we investigated the expression levels of lncRNAs in the blood of LVNC patients and healthy subjects to identify differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…GSEA revealed that NLRP3 in ammasome (GO), bile secretion and thyroid hormone synthesis (KEGG) were enriched in LVNC, consistent with the former study [15]. In addition, the "interstitial matrix", "endocytosis" terms were positively enriched.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…GSEA revealed that NLRP3 in ammasome (GO), bile secretion and thyroid hormone synthesis (KEGG) were enriched in LVNC, consistent with the former study [15]. In addition, the "interstitial matrix", "endocytosis" terms were positively enriched.…”
Section: Discussionsupporting
confidence: 87%
“…We obtained human LVNC related genes from the Gene Expression Omnibus database (GEO, https://www.ncbi.nlm.nih.gov/geo). GSE178582 dataset contains blood samples from 6 LVNC patients and 6 healthy controls, pro ling mRNA and lncRNA expression [15]. GSE178582 dataset was based on GPL16956 (Agilent-045997 Arraystar human lncRNA microarray V3).…”
Section: Microarray Dataset Download and Pre-processingmentioning
confidence: 99%
See 2 more Smart Citations